Is climate warming more consequential towards poles? The phenology of Lepidoptera in Finland. (24th September 2013) - Valtonen, Anu; Leinonen, Reima; Pöyry, Juha; Roininen, Heikki; Tuomela, Jukka; Ayres, Matthew P.
Abstract The magnitude and direction of phenological shifts from climate warming could be predictably variable across the planet depending upon the nature of physiological controls on phenology, the thermal sensitivity of the developmental processes and global patterns in the climate warming. We tested this with respect to the flight phenology of adult nocturnal moths (3.33 million captures of 334 species) that were sampled at sites in southern and northern Finland during 1993–2012 (with years 2005–2012 treated as an independent model validation data set). We compared eight competing models of physiological controls on flight phenology to each species and found strong support for thermal controls of phenology in 66% of the species generations. Among species with strong thermal control of phenology in both the south and north, the average development rate was higher in northern vs. southern populations at 10 °C, but about the same at 15 and 20 °C. With a 3 °C increase in temperature (approximating A2 scenario of IPPC for 2090–2099 relative to 1980–1999) these species were predicted to advance their phenology on average by 17 (SE ± 0.3) days in the south vs. 13 (±0.4) days in the north. The higher development rates at low temperatures of poleward populations makes them less sensitive to climate warming, which opposes the tendency for stronger phenological advances in the north from greater increases in temperature.